Genome Data Provides High Support for Generic Boundaries in Burkholderia Sensu Lato - Beukes, Chrizelle W.; Palmer, Marike; Manyaka, Puseletso; Chan, Wai Y.; Avontuur, Juanita R.; van Zyl, Elritha; Huntemann, Marcel; Clum, Alicia; Pillay, Manoj; Palaniappan, Krishnaveni; Varghese, Neha; Mikhailova, Natalia; et al. (Frontiers in microbiology, 2017)
Although the taxonomy of has been extensively scrutinized, significant uncertainty remains regarding the generic boundaries and composition of this large and heterogeneous taxon. Here we used the amino acid and nucleotide sequences of 106 conserved proteins from 92 species to infer robust maximum likelihood phylogenies with which to investigate the generic structure of sensu lato. These data unambiguously supported five distinct lineages, of which four correspond to sensu stricto and the newly introduced genera , , and . The fifth lineage was represented by . Based on these findings, we propose 13 new combinations for those species previously described as members of but that form part of . These findings also suggest revision of the taxonomic status of as it is does not form part of any of the genera currently recognized in sensu lato. From a phylogenetic point of view, sensu stricto has a sister relationship with the + clade. Also, the lineages represented by and , respectively, emerged prior to the radiation of the sensu stricto+ + clade. Our findings therefore constitute a solid framework, not only for supporting current and future taxonomic decisions, but also for studying the evolution of this assemblage of medically, industrially and agriculturally important species.